Transformation numérique du jam : de l’improvisation à la composition collective - Sylvain Martet; Elsa Fortant (Communiquer)
In 2020 in Quebec, the COVID-19 pandemic led to the cancellation of many musical events. In addition to the concerts, it was also the jam sessions that had to stop. These events usually bring together music lovers for collective improvisation sessions framed by rules that vary depending on the location, the participants, and the genre of music. This article focuses more specifically on a community of electronic music producers and fans who have chosen to transpose into the digital environment the jam event they used to organize. Our research aims to understand what digital transposition does to collective creation and through which technical devices it materializes. In the face of both technical and organizational constraints and limitations, the meaning of the jam is evolving from music played together to music produced and composed collectively. Thus, our research shows that the will to develop a temporary collective, common project encourages participants to negotiate with the potential format of the event.